In-Vitro Antioxidant Activity Studies On The Flowers Of Tagetes Erecta L. (Compositae) - BASAVARAJ V CHIVDE,; KARNAKUMAR V BIRADAR,; RAJABHAU S SHIRAMANE,; KAMSHETTY V MANOJ, (International Journal of Pharma and Bio Sciences, 2011)
In the present study, in Vitro Antioxidant studies were performed on the ethanolic extract of Tagetes erecta flowers. During the study preliminary phytochemical analysis were carried out on ethanolic extract of flowers of Tagetes erecta and found the presence of Alkaloids, Flavonoids, Proteins, Steroids and tannins. For the study of in Vitro antioxidant activity three different assays like DPPH, reducing power and super oxide radical scavenging activity at different concentrations were used. In all the three assay, Tagetes erecta showed better reducing power than the standard (i.e. ascorbic acid), and super oxide anion scavenging activity and DPPH antioxidant activity showed less than standard. However, ethanolic extract of Tagetes erecta demonstrated antioxidant property in all the in Vitro models.